Distortions of Metallic Objects in EM34 Apparent Conductivity Readings - Chibane, Pedro Henrique da Silva; Silva, Caroline Urenha [UNESP]; Mendonca, Carlos Alberto; Ofterdinger, Ulrich (Environmental Engineering Geophysical Soc, 2024)
Metallic structures are a common noise source in Slingram electromagnetic surveys because they interact with the primary magnetic field generated by the transmitter coil and create a secondary magnetic field that distorts the apparent conductivity readings from a layered or homogeneous subsurface. The main challenge is understanding how their influence varies depending on the loop configuration and the distance at which the surface structure no longer distorts the apparent conductivity readings. We propose a methodology that integrates experimental techniques and numerical modeling to elucidate the distortions induced by a fence-like structure placed at varying distances from the coils of a low-induction conductivity meter. Additionally, we aim to evaluate the model responses using numerical simulations with electromagnetic systems operating at higher frequency ranges. To quantify the distortions in apparent conductivity, we conducted field measurements by keeping the electromagnetic coils in a fixed position while changing the placement of the conductive structure. The readings obtained before installing the conductive structure were used as the background reference response to accurately determine the distortions. The same experimental procedure was tested in terrains with different resistivities to evaluate the changes caused by the same structure in different backgrounds. Our results show that this approach allowed us to infer that the deviations in apparent conductivity caused by the presence of the fence are more noticeable where the background resistivity is higher. However, these deviations were observed only for short distances of about 1/5 to 1/2 of the coil separation for the evaluated targets. The integration between the experimental survey and the numerical modeling suggests that distortion increases when the instrument is operated at induction numbers higher than similar to 0.2. For all tested conductivity models and frequency ranges, minor distortions were observed with the vertical coplanar coil configuration compared to the horizontal coplanar configuration for the transmitter-receiver pair. Negligible distortions were observed for fences with unconnected wires, suggesting minor interference from loose metallic objects on the ground surface that do not form closed loops, favoring EM induction.